DNA Methylation-Dependent Dysregulation of GABAergic Interneuron Functionality in Neuropsychiatric Diseases - Linde, Jenice; Zimmer-Bensch, Geraldine (Frontiers in Neuroscience, 2020)
Neuropsychiatric diseases, such as mood disorders, schizophrenia and autism, represent multifactorial disorders, differing in causes, disease onset, severity, and symptoms. A common feature of numerous neuropsychiatric conditions are defects in the cortical inhibitory GABAergic system. The balance of excitation and inhibition is fundamental for proper and efficient information processing in the cerebral cortex. Thus, altered inhibition is suggested to account for pathological symptoms like cognitive impairments and dysfunctional multisensory integration. While it became apparent that most of these diseases have a clear genetic component, environmental influences emerged as an impact of disease manifestation, onset, and severity. Epigenetic mechanisms of transcriptional control, such as DNA methylation, are known to be responsive to external stimuli, and are suspected to be implicated in the functional impairments of GABAergic interneurons, and hence, the pathophysiology of neuropsychiatric diseases. Here, we provide an overview about the multifaceted functional implications of DNA methylation and DNA methyltransferases in cortical interneuron development and function in health and disease. Apart from the regulation of GABA-related genes and genes relevant for interneuron development, we discuss the role of DNA methylation-dependent regulation of synaptic transmission by the modulation of endocytosis-related genes as potential pathophysiological mechanisms underlying neuropsychiatric conditions. Deciphering the hierarchy and mechanisms of changes in epigenetic signatures is crucial to develop effective strategies for treatment and prevention.